Clinical therapeutic efficacy of mycophenolate mofetil in the treatment of SARDS in dogs—a prospective open‐label pilot study. (31st January 2018) - Young, Whitney M.; Oh, Annie; Williams, Jonathan G.; Foster, Melanie L.; Miller, William W.; Lunn, Katharine F.; Mowat, Freya M.
Abstract: Objective: Sudden acquired retinal degeneration syndrome (SARDS) is a leading cause of irreversible blindness in dogs, yet no treatment has been objectively evaluated, or proven to be effective. Consensus of opinion is that SARDS is immune‐mediated, although corticosteroid medications may exacerbate associated systemic signs. We examined the effect of sole‐agent treatment with mycophenolate mofetil (MMF), a potent immunosuppressive medication unlikely to exacerbate associated systemic signs. Animals studied: Ten client‐owned dogs with SARDS prospectively recruited within 6 weeks of vision loss. Procedures: Clinical history, findings of systemic and ophthalmic examinations, blood parameters, visual navigation ability, electroretinography, and optical coherence tomography (OCT) were collected at baseline and at recheck after approximately 6 weeks of treatment with 10 mg/kg q 12 h of oral MMF. Results: Twenty percent of dogs (2/10) experienced side effects (diarrhea, vomiting, lethargy), which resolved with reduction in dose to 8 mg/kg q12 h. No significant changes in systemic signs, physical examination findings, or laboratory test results were detected at the recheck examination. Compared with baseline, visual ability significantly declined at the recheck examination, and the amplitude of a slow‐onset negative waveform noted on dark‐adapted electroretinography was reduced at the recheck examination. The outer retinal layers were significantly thinner at the recheck examination as measured by OCT. Conclusions: Mycophenolate mofetil as a sole agent has no measureable positive effect on physical health, vision, or retinal structure following a 6‐week trial period. Further studies are needed to evaluate other treatment options for SARDS.